Pengaruh model pembelajaran discovery learning berbantuan media benda konkret terhadap hasil belajar IPA - Rosyida Husni; Ari Suryawan; Puji Rahmawati (Borobudur Educational Review, 2022)
This study aims to determine the effect of the Discovery Learning model assisted by concrete objects on the science learning outcomes of fifth-grade students at MI Al-Islam Ngepanrejo, Bandongan. This research is Pre-Experimental research with a design (One Group Pretest-Postest). The samples taken for the study were all students of class V totaling 16 people. The sampling technique used was a saturated sample. The method of data collection was carried out using the test in the form of pretest and posttest questions in the form of multiple-choice and observation. Validity test to measure the pretest and posttest questions using Product Moment, reliability using Cronbach’s Alpha the data analysis technique in research uses testing normality by using the Shapiro-Wilk and hypothesis testing using The Wilcoxon sign rank test with help of IBM SPSS version 25.00 for windows program. The results showed that the Discovery Learning model assisted by concrete objects had a positive effect on science learning outcomes. This is evidenced by the result of the analysis of the hypothesis of the pretest and posttest data regarding the matter of heat and transfer using the Wilcoxon sign rank test with the result showing that the Z value obtained is -3,521 with Asymp Sig. 2 tailed of 0,000 (0,000<0,05). Based on the results of the analysis and discussions, there is a difference in the average score of the pretest result 45 and the posttest with an average score of 75. The result can be concluded that the use of the Discovery Learning model assisted by concrete objects has a positive effect on science learning outcomes.